Impact of Domestic Violence on Girl-Child in Secondary Schools in Bukusu Sub-County Manafwa District - Lornah Kakayi (Uganda Christian University, 2024)
ABSRACT This study aimed at ascertaining the impact of domestic violence on girl-child in secondary schools in Bukusu sub-county, Manafwa District. The study was guided by the following specific objectives: to examine the forms of domestic violence on girl-child in secondary schools in Bukusu Sub-county Manafwa District, to analyse the causes of domestic violence on the academic performance in secondary schools in Bukusu Sub-county Manafwa District, to establish the effects of domestic violence on the girl-child in Bukusu Sub-county. The study adopted a descriptive research design employing both quantitative and qualitative approaches that targeted; parents, head teachers, teachers, learners and community leaders who were expected to provide the required information. Questionnaires, interview guide and observation checklists were to collect data from various respondents. To get quality data, the researcher ensured that the instruments were valid by conducting a preliminary survey and SPSS to determine their reliability. The findings from the study indicated that domestic violence affecting academic performance in secondary schools in Bukusu sub-county is in different forms and greatly hinders the learners‟ progress and progress as much as several attempts have been made to mitigate it. The researcher therefore recommended; awareness campaigns for domestic violence, enforcement of the law advocacy for human rights, the teaching of Christian religious education to be compulsory as a strategy for moral formation. The church should also intensify its mission to the people as a way of correcting human error and restoring peace, love, care and harmony in society.